Optimization of coconut husk as pore forming agent in porous ceramic using response surface methodology (rsm) statistical design - Nur Syazwana Adzhar (2024)
Coconut husk is the most well-known fibrous waste product from coconut tree cultivation. Coconut husk contains a high concentration of lignin, which makes it exceptionally elastic, durable, and resistant to rotting. Coconut husk was suitable to be as pore-forming agents in porous ceramic. Coconut husk was sieved to 250μm before mixing with the kaolin clay. Porous ceramic material was developed through the incorporation of kaolin clay and coconut husk, then make the composition of coconut husk with 10 wt.%, 20 wt.% and 30 wt.%. The slurry is dried at 100°C for 24 hours before crush it into powder. Lastly, compacted the powder mixture and sintered at 850°C, 900°C and 950°C before we do characterization. The characterization used in this study were physical properties like water absorption, apparent porosity and bulk density, mechanical properties like compressive strength, FTIR for coconut husk and XRD for kaolin clay and porous ceramic. In this study, response surface methodology (RSM) statistical design was applied to optimize the coconut husk added and sintering temperature for the porous ceramic. Statistical analysis of RSM such as Central Composite Design (CCD), includes model adequacy checking, analysis of variance (ANOVA), main effect, interaction plot and contour plot. The factor (experimental parameters) involved were weight percentage of coconut husk (wt.%), whilst the responses (final properties of ceramics) investigated were water absorption, apparent porosity, bulk density and compressive strength. The optimal sintering temperature and composition in the contour plot where water absorption, apparent porosity must be as minimum and bulk density and compressive is at maximum, which shown to be around 900°C with 10 wt.% coconut husks